Monitoring vesicular trafficking in cellular responses to stress. - Kepp, Oliver; Galluzzi, Lorenzo (Methods in cell biology, 2021)
Monitoring Vesicular Trafficking in Cellular Responses to Stress, Volume 164 in the Methods in Cell Biology series, highlights new advances in the field, with this new volume presenting interesting chapters on a variety of timely topics. Each chapter is written by an international board of authors.